THE ONTHOLOGICAL VOCATION OF BEING MORE: LIMIT-SITUATIONS - APPROXIMATING FREIRE AND VIEIRA PINTO - Freitas, André Luis Castro de; de Araujo Freitas, Luciane Albernaz (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
The text intends to make approximations between the thoughts of Paulo Freire and Álvaro Vieira Pinto. From a critical descriptive study, the intention is to list assumptions that demonstrate, in the authors' conception, the making of a more humane and liberating popular education. Education that does not accept the fatalism of the precariousness of the human being exposed to suffering, but understands a radical action of transformation from a dialectic relation between conditioning and freedom. Reflected on the frontier, not between being and nothing, but between being and being more, when from free acts to think the limit-situations it is possible to constitute, on the plane of history, the limit-acts. The research has as its starting point the dialectical-dialogical method of Paulo Freire.